Distribution of Alkaloid‐Rich Plant Species in Shortgrass Steppe Vegetation - Donald L. Hazlett; Neil W. Sawyer (Conservation Biology, 1998)
We investigated the distribution of alkaloid‐rich plant species in shortgrass steppe vegetation. The intent was to identify and to determine if alkaloid‐rich species were more prevalent in certain habitats or life forms and to determine if ethnomedicinal accounts were an indicator of alkaloid‐rich taxa. Alkaloid screening tests were performed on plant tissues from 77% of 275 plant species that occurred at the Central Plains Experimental Range. There were alkaloid‐positive results for 10% of all species tested. When alkaloid‐rich plant taxa were categorized by habitat, none of six habitats had a significantly greater percentage of alkaloid‐rich species. Nevertheless, about three‐fourths of all plant taxa and of all alkaloid‐rich taxa occurred in “water‐enriched” habitats, which composed less than 20% of the study area. A higher percentage of alkaloid‐positive species was found among forbs, especially biennial forbs, than among graminoids. There were ethnomedicinal reports for 23% of all study species. The percentage of alkaloid‐rich species was similar for species with and without ethnomedicinal uses. A natural product database indicated that 46% of native plant species in the study area had been screened and had tested positive for at least one type of biological activity. The chemical structures of plant chemicals had been identified for only 12% of all species, however. Technologies are rapidly developing to screen for and utilize plant chemical resources. Therefore, conservation biologists should be aware of plant species and habitats that have unique or potentially useful plant chemicals. Land managers can use baseline plant chemical data to begin an evaluation of current policies in regard to the protection of this natural resource. Distribución de Especies de Plantas Ricas en Alcaloides en Vegetación de Estepas de Pastos Cortos Investigamos la distribución de los quimicos alcaloides en plantas de la vegetación de la pradera. El propósito fue identificar y determinar si las especies de plantas con alcaloides fueron más predominantes en ciertos hábitats o formas de vida y determinar si la información etnobotànica fue un buen indicador para especies de plantas que tienen alcaloides. Se hicieron ensayos químicos para alcaloides usando los tejidos de 77% de las 275 especies de plantas que ocurrieron en el área del estudio. Resultados positivos ocurrieron en 10% de las especies ensayadas. Ninguno de los seis hábitats tuvieron significativamente más especies con ensayos positivos para alcaloides. Casi tres‐cuartos de todas las especies en el área del estudio ocurrieron en los hábitats que recibieron, debido a su posición topográfica y suelos, agua adicional. Estos hábitats constituyeron menos del 20% del área del estudio. Había un porcentaje mayor de especies con resultados positivos con alcaloides entre plantas no gramíneas, especialmente entre bianuales, que entre plantas gramíneas. Reportes etnobotánicos fureon encontrados en 23% de las especies estudiadas. No hubo un porcentaje mayor de ensayos positivos para alcaloides entre especies de plantas con reportes etnobotánicos que entre especies que no tenían reportes etnobotánicos. Estudios químicos reportados en la literatura indicaran que 46% de las especies de plantas en el lugar de este estudio tenían por lo menos un reporte clínico de actividad biológica. Sin embargo, investigaciones para determinar la estructura química de plantas han sido realizados solamente en 12% de las especies. Tecnologías nuevas están desarrollándose rápidamente para ensayar y utilizar los recursos químicos de las plantas. Por lo tanto, los biólogos en favor de la conservación deben darse cuenta de cuáles son las especies de plantas y los hábitats donde se encuentran químicos útiles. Entonces será posible evaluar si las decisiones administrativas actuales son adequadas para la protección de este recurso natural.